Multiple Sclerosis: Effects of Cognitive Rehabilitation on Structural and Functional MR Imaging Measures—An Explorative Study - Filippi, Massimo; Riccitelli, Gianna; Mattioli, Flavia; Capra, Ruggero; Stampatori, Chiara; Pagani, Elisabetta; Valsasina, Paola; Copetti, Massimiliano; Falini, Andrea; Comi, Giancarlo; Rocca, Maria A. (Radiology, 2012)
To evaluate brain changes after cognitive rehabilitation in patients with clinically stable relapsing-remitting (RR) multiple sclerosis (MS) by using neuropsychologic assessment and structural and functional magnetic resonance (MR) imaging techniques. The study was conducted with approval of the involved institutional review boards. Written informed consent was obtained from each participant. Twenty patients with RR MS and cognitive deficits at baseline were randomly assigned to undergo treatment (n = 10), which entailed computer-assisted cognitive rehabilitation of attention and information processing and executive functions, or to serve as a control subjects (n = 10) without cognitive rehabilitation. All patients underwent a standardized neuropsychologic assessment and MR imaging at baseline and after 12 weeks. Changes in gray matter (GM) volumes on three-dimensional T1-weighted images and changes in normal-appearing white matter (NAWM) architecture on diffusion-weighted images were assessed. Changes in functional activity at functional MR imaging during the Stroop task and at rest were also investigated by using linear models. As compared with their performance at baseline, the patients in the treatment group improved at tests of attention and information processing and executive functions. Neither structural modifications to GM volume nor modifications to NAWM architecture were detected at follow-up in both groups. Functional MR imaging demonstrated modifications of the activity of the posterior cingulate cortex (PCC)/precuneus and dorsolateral prefrontal cortex (PFC) during the Stroop task, as well as modifications of the activity of the anterior cingulum, PCC and/or precuneus, left dorsolateral PFC, and right inferior parietal lobule at rest in the treatment group compared with the control group. In the treatment group, functional MR imaging changes were correlated with cognitive improvement (P < .0001 to .01). Rehabilitation of attention and information processing and executive functions in RR MS may be effected through enhanced recruitment of brain networks subserving the trained functions.